Jawabanmu

2014-05-17T15:57:58+07:00
(1-sinA-cosA)² - 2(1-sinA-CosA)-2sinAcosA
= 1 - SinA - cosA - SinA + Sin²A + SinACosA - CosA +  SinA CosA + Cos²A -2 + 2SinA +        2CosA - 2SinACosA
= 1-2 - 2SinA + 2SinA - 2CosA + 2CosA + 2SinACosA - 2SinAcosA + Sin²x + Cos²x
= -1 + Sin²A + Cos²A
= -1 + 1
= 0
1 5 1
Jawaban paling cerdas!
2014-05-17T16:13:53+07:00
( 1-sin A- cos A)² - 2(1-sin A-cos A)- 2 sin A cos A
= 1- 2 sin A - 2 cos A + 2 sin A cos A + sin² A + cos² A - 2 + 2 sin A + 2 cos A - 2 sin A cosA
= -1 + sin²A + cos² A
= -1 + 1
= 0
1 5 1